Using the Keywords to Explain the Bonobo Distribution as an Effect of Human Perception of the Species - Inogwabini, Bila-Isia; Leader-Williams, Nigel (American Journal of Human Ecology, 2012)
Quantitative and qualitative analyses of ecological factors conducted on the distribution of the bonobos of the Lake Tumba Landscape did not fully explain the actual distribution of bonobos in that part of their range. Hence, the aim of this paper was to study the human cultural landscape of the region to shed light on questions raised by differentiated bonobo abundance. This was conducted using a combination of methods, including key word approach through focus group sessions, the Dempster combination rule to calculate the strength of belief and overlaying maps of ethnic groups and that of abundance of bonobos to see if the distribution of ethnic groups correlated with the density of the bonobos. Paired t-tests were used to assess difference in strength of belief between ethnic groups. Focal groups collected 113 stories, centered on six main themes, of which the most striking feature was the humanization of bonobos, with themes such as ‘making of fire’ (23.8%), ‘crying by bonobos’ (21.2%), ‘bonobo as ancestors of human beings’ (7.9%) and ‘rescuing people from imminent danger’ (6.1%). Calculated values for the strength of belief varied between ethnic groups; the Bateke held the highest (63%) strength of belief, while the weakest (14%) strength of belief was held in the cosmopolitan centers. Paired t-tests indicated that the strength of belief significantly differed (all p < 0.05, df = 29) between the Bateke and the two other ethnic groups. We concluded that strength of beliefs depicted the fact that Bateke, through their traditional taboos, had protected bonobos over centuries that they have been sharing the same forests.